2015
DOI: 10.1002/ece3.1598
|View full text |Cite
|
Sign up to set email alerts
|

The avoidance strategy of environmental constraints by an aquatic plant Potamogeton alpinus in running waters

Abstract: Aquatic plants anchored in streams are under pressure from various constraints linked to the water flow and display strategies to prevent their damage or destruction. We assume that the responses of aquatic plants to fast-water flow are a manifestation of a trade-off consisting in either maximizing the resistance to damage (tolerance strategy) in minimizing the hydrodynamic forces (avoidance strategy), or both. Our main hypothesis was that Potamogeton alpinus demonstrate the avoidance strategy. We analyzed arc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…This is confirmed by the differences in the results of the three-point bending test between seasons, where in 2017 plants were characterised by lower flexural rigidity connected with higher flexural modulus, which was responsible for elastic deformation, meaning the return of the plant to its original shape after the load was removed. The higher discharges and water velocities could cause the adoption of an avoidance strategy to prevent damage or destruction, which was characterised by an increase in shoot elasticity in line with the results of the study by Robionek et al [31]. According to Schutten et al [32] and Puijalon et al [33], aquatic plants are flexible and adjust to living factors by bending with the flow direction.…”
Section: Discussionsupporting
confidence: 73%
“…This is confirmed by the differences in the results of the three-point bending test between seasons, where in 2017 plants were characterised by lower flexural rigidity connected with higher flexural modulus, which was responsible for elastic deformation, meaning the return of the plant to its original shape after the load was removed. The higher discharges and water velocities could cause the adoption of an avoidance strategy to prevent damage or destruction, which was characterised by an increase in shoot elasticity in line with the results of the study by Robionek et al [31]. According to Schutten et al [32] and Puijalon et al [33], aquatic plants are flexible and adjust to living factors by bending with the flow direction.…”
Section: Discussionsupporting
confidence: 73%
“…observations in Bouma et al 2010;Bouma et al 2013). A similar strategy to survive under high flow and wave-induced velocities by avoiding high drag forces through reconfiguration is also known for flexible sea grasses (Infantes et al, 2011;Peralta et al, 2008) and freshwater macrophytes (O'Hare et al, 2007;Puijalon et al, 2011;Robionek et al, 2015).…”
Section: 2 Susceptibility Of Salt Marsh Vegetation To Physical Damagmentioning
confidence: 88%
“…Aquatic plants grown in streams have various constraints linked to the water flow and adopt strategies to prevent damage due to water pressure and other hydrodynamic forces [58]. As an example, the architecture traits of the modules of Potamogeton alpinus (Potamogetonaceae) from slow- and fast-flowing streams have been studied [59]. It was found that in fast-flowing waters, the presence of floating leaves stabilized the vertical position of stem and caused elongation of submerged leaves; together with a reduction in shoot diameter, this reduced the pressure of the water.…”
Section: Environmental Factors That Induce Heterophyllymentioning
confidence: 99%
“…It was found that in fast-flowing waters, the presence of floating leaves stabilized the vertical position of stem and caused elongation of submerged leaves; together with a reduction in shoot diameter, this reduced the pressure of the water. In addition, plants grown in fast-flowing conditions are more resistant to stretching than others grown in standing waters, which means that stems from fast-flowing conditions are more elastic and therefore less prone to damage by stretching forces [59,60].…”
Section: Environmental Factors That Induce Heterophyllymentioning
confidence: 99%